Kinematic analysis in dogs with spinal reflex locomotion - Alves, Beatriz Borges (2023)
Spinal cord injury (SCI) is a commonly event observed in dogs following intervertebral disc disease and spinal trauma and can lead to clinical conditions of patients in grade0, according to the Modified Frankel Scale (MFS). Functional neurorehabilitation aimstorestore the patient’s independence and functionality, which is essential for subjects classifiedas grade 0 according to MFS. In these patients the goal of functional neurorehabilitation(FNR)is to recovery deep pain perception (DPP) or to obtain Spinal Reflex Locomotion (SRL). In humans and animals, kinematic gait analysis has been widely used to assess gait abnormalities associated with orthopaedic and neurologic pathologies. This objectiveandsensitive method constitute an accurate outcome measure for functional gait analysis indogswith SRL. This dissertation aims to use kinematic gait analysis (1) to assess and describetheambulation of two dogs with locomotion by reflexes, comparing with two proprioceptiveataxic thoracolumbar (T3-L3) dogs, and (2) to evaluate the variability of specificgait parameters in dogs with SRL over time. Four chondrodystrophic dogs diagnosed with acute thoracolumbar (T3-L3) spinal corddisease, submitted to surgery and to the same neurorehabilitation protocol were includedinthis study. They were admitted on the study one year after medical discharge. Dogs weredivided in two groups: two dogs for the study group (SG) with SRL; and two dogs for thecontrol group (CG) with a proprioceptive ataxic gait. A kinematic gait analysis was performedto assess temporospatial parameters (step time, stride time, stance time, swing time, relativestance time, relative swing time, stride frequency, step length and swing phase) for all dogs. The results showed a high variability in dogs with SRL over time, specificallyinsteptime coefficient of variation (CV) and step length CV which was six times higher whencompared to proprioceptive ataxic dogs. Despite the large variability obtained in stridetimeCV, with 2.14 for the SG and 0.64 for the CG, was observed a similar stride time meanbetween groups. Within the SG, the variability evaluation in gait parameters (CsVfromtemporal variables and swing phase of spatial variables) showed a slight tendency to decreasethroughout time. Furthermore, was found in the SG a strong negative correlation betweenstride frequency and the following variables stride time, stance time, step length andrelativestance time. The CG revealed a low variability and a more modulated gait. The present study allowed to conclude that dogs with SRL have a large variationinspatiotemporal gait parameters, which is in accordance with literature. The tendencytothetemporal variables to decrease over time, suggests a possible neural reorganizationandlocomotion modulation, essential to maintain a coordinated ambulation. This study should be continued in order to be a useful tool in a clinical settingtohelpand complement the neurorehabilitation work and evaluate the patient’s response to treatment.